Investigating decimal misconceptions among primary students in Brunei: a preliminary study - Khalid, Madihah (Education Technology Centre, Universiti Brunei Darussalam, 2006)
Misconceptions among decimals have been investigated since the early 1980s. Studies done in several countries showed that students tend to make mistakes when asked to choose which is larger from pairs of decimal numbers. A similar study was undertaken to investigate Brunei’s upper primary students’ misconceptions in comparing these decimal numbers. Results showed the existence of these misconceptions among the students. Some differences between the results in Brunei and Australian were investigated. This paper also offers suggestions for instructional approaches that can be used as a guide by teachers in Brunei, in line with the new curriculum introduced since January 2006. The results and suggestions will hopefully contribute to shaping the future of mathematics education in Brunei. [In H.S. Dhindsa, et al. (Eds) (2006). Shaping the future of science mathematics and technical education (pp. 193-201). Gadong, Brunei: ETC – Universiti Brunei Darussalam].